O caráter objetivo-vinculante da responsabilidade social empresarial no Brasil - Simões, Jamili (2025)
The thesis aims to address the topic of Business and Human Rights through the study of Corporate Social Responsibility (CSR) and its binding-objective nature. In order to provide a comprehensive understanding of the subject, the research begins with the conceptualization of Human Rights and their historical evolution, including the emergence of International Human Rights Law. This includes an analysis of key developments such as the creation of the United Nations (UN) and the Universal Declaration of Human Rights (UDHR), a historic milestone in the proclamation of fundamental rights for all human beings. It further explores the applicability of Human Rights to legal entities, the influence of the UN Guiding Principles on Business and Human Rights (as formulated by John Ruggie), and the relationship between CSR and contemporary concepts such as sustainable development, sustainability, and ESG (Environmental, Social, and Governance), which are deeply interwoven with this thematic field and hold significant relevance today. Subsequently, the study undertakes a detailed analysis of Corporate Social Responsibility, focusing on its core characteristics, comparative legal frameworks in foreign jurisdictions, and the challenge of assigning binding legal force to CSR through hard law mechanisms. The thesis concludes with proposals for regulatory improvement, both at the international treaty level and within the domestic legal context, aiming to render CSR both viable and effectively enforceable within corporate structures. Additional proposals include the implementation of human rights due diligence and the incorporation of artificial intelligence as a regulatory tool. A case study of Vale S.A. is also presented as a practical illustration of the challenges and possibilities in this field. In light of this comprehensive approach, the research seeks to answer the following central question: Is Corporate Social Responsibility of an objective and binding nature by virtue of being rooted in human rights, and is it possible to enhance CSR regulation either through an international treaty or within the Brazilian legal framework? The subject matter is organized into three chapters, supported by national and international legal scholarship, foreign and domestic legislation relevant to the theme, as well as guidelines derived from international norms and partnerships with the United Nations for the promotion and protection of human rights within business contexts. Methodologically, the study adopts a hypothetico-deductive approach, with bibliographic, doctrinal, and documentary research methods. The thesis is situated within the field of Business Law, specifically under Research Line 2: Transnational Corporations and Regulation.